Bio-based reactive diluents as sustainable replacements for styrene in MAESO resin. Issue 25 (12th April 2018) - Zhang, Yuehong; Li, Yuzhan; Thakur, Vijay Kumar; Wang, Liwei; Gu, Jiyou; Gao, Zhenhua; Fan, Bo; Wu, Qiong; Kessler, Michael R.
Abstract : This paper reports four promising, sustainable reactive diluents to completely replace styrene for a commercially available MAESO resin. Abstract : Four different biorenewable methacrylated/acrylated monomers, namely, methacrylated fatty acid (MFA), methacrylated eugenol (ME), isobornyl methacrylate (IM), and isobornyl acrylate (IA) were employed as reactive diluents (RDs) to replace styrene (St) in a maleinated acrylated epoxidized soybean oil (MAESO) resin to produce bio-based thermosetting resins using free radical polymerization. The curing kinetics, gelation times, double bond conversions, thermal–mechanical properties, and thermal stabilities of MAESO-RD resin systems were characterized using DSC, rheometer, FT-IR, DMA, and TGA. The results indicate that all four RD monomers possess high bio-based carbon content (BBC) ranging from 63.2 to 76.9% and low volatilities (less than 7 wt% loss after being held isothermally at 30 °C for 5 h). Moreover, the viscosity of the MAESO-RD systems can be tailored to acceptable levels to fit the requirements for liquid molding techniques. Because of the introduction of RDs to the MAESO resin, the reaction mixtures showed an improved reactivity and an accelerated reaction rate. FT-IR results showed that almost all the CC double bonds within MAESO-RD systems were converted. The glass transition temperatures ( T g ) of the MAESO-RDs ranged from 44.8 to 100.8 °C, thus extending the range of application. More importantly, the T g of MAESO-ME resin (98.1 °C) was comparable to that of MAESO-St resin (100.8 °C). Overall, this work provided four potential RDs candidates to completely replace styrene in the MAESO resin, with the ME monomer being the most promising one.